2020
DOI: 10.1186/s13018-020-01905-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor outcome in cervical spondylotic myelopathy patients underwent anterior hybrid approach: focusing on change of local kyphosis

Abstract: Objective: This study was a retrospective multivariable analysis for risk factors of poor outcome in patients who underwent anterior hybrid approach, and discussed the causes of worsening of postoperative local alignment. Methods: A total of 86 patients with progressive spinal cord compression and local kyphosis underwent an anterior hybrid approach (ACDF+ACCF), between June 2011 and June 2017. We evaluated clinical outcome by the Japanese Orthopaedic Association (JOA) score and recovery rate. Patients were di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Experimental models of CSM have revealed that cervical kyphotic deformity is associated with demyelination, atrophy, and neuronal loss of the anterior horn, together with a decreased vascular supply of the anterior spinal cord [9,31]. Contrary to our results, a correlation between the CSM severity and the preoperative [32] or postoperative [33] local kyphotic deformity was found in recent studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Experimental models of CSM have revealed that cervical kyphotic deformity is associated with demyelination, atrophy, and neuronal loss of the anterior horn, together with a decreased vascular supply of the anterior spinal cord [9,31]. Contrary to our results, a correlation between the CSM severity and the preoperative [32] or postoperative [33] local kyphotic deformity was found in recent studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it remains unclear which patients experience poor QOL improvement after surgery. To date, most of the reports on surgical outcomes have used the Japanese Orthopedic Association score for the assessment of cervical myelopathy (C-JOA) to evaluate neurological status [ 7 9 ]. However, based on international assessment standards, there are several problems associated with C-JOA scores including that (1) they do not reflect the patient's self-assessment of pain, numbness, and health status and (2) they are assessed primarily from the physician's perspective [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis status was evaluated by a 6-month post-operative improvement rate for the JOA score. The calculation formula of the JOA improvement rate is as follows: the JOA improvement rate = (post-operative JOA score—pre-operative JOA score)/(17—pre-operative JOA score) × 100% ( 14 ). A JOA score improvement rate of more than 75% is excellent, 50–74% is good, 25–49% is acceptable, and <25% is poor ( 15 ).…”
Section: Methodsmentioning
confidence: 99%